2016
DOI: 10.3109/01677063.2016.1155571
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofEPHX1andCYP3A4*22genetic polymorphisms on carbamazepine metabolism and drug response among Tunisian epileptic patients

Abstract: The aim of this study was to evaluate the impact of polymorphisms in the EPHX1 (c.416A > G, c.337T > C) and CYP3A4*22 genes involved in carbamazepine (CBZ) metabolism and pharmacoresistance among 118 Tunisian patients with epilepsy under maintenance dose of CBZ. These genetic polymorphisms were analyzed by PCR-RFLP. Associations between plasma CBZ concentration, CBZ-E concentration, maintenance doses and metabolic ratio (CBZ-E:CBZ, CBZ-D:CBZ-E) were analyzed with each polymorphism. Both variants of EPHX1 c.416… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 18 publications
1
10
1
Order By: Relevance
“…Polymorphisms in CYP3A4 and EPHX1 have been shown to associate with interindividual variability of CBZ metabolism. 14,15 We did not observe even nominally significant associations between SNPs in CYP3A4 and CBZ metabolic ratio. It had been reported that homozygous carriers of the EPHX1 c.416A>G SNP (rs2234922) seemingly show a reduced CBZ metabolism, as measured by a significantly decreased metabolic ratio.…”
Section: Resultscontrasting
confidence: 66%
“…Polymorphisms in CYP3A4 and EPHX1 have been shown to associate with interindividual variability of CBZ metabolism. 14,15 We did not observe even nominally significant associations between SNPs in CYP3A4 and CBZ metabolic ratio. It had been reported that homozygous carriers of the EPHX1 c.416A>G SNP (rs2234922) seemingly show a reduced CBZ metabolism, as measured by a significantly decreased metabolic ratio.…”
Section: Resultscontrasting
confidence: 66%
“…For EPHX1 c.416A>G polymorphism, the adjusted concentrations of CDR CBZ , CDR CBZE and CDR CBZD were reported in 4 [7,8,25,31], 3 [7,8,31] and 3 [7,8,31] articles, respectively. A total of 646 epilepsy patients treated by CBZ in 3 studies were included with statistically significant association between (AA vs GG) ,(AG vs GG) models in EPHX1 c.416A>Gpolymorphisms and CDR CBZD (OR = 0.483 (95% CI: 0.011˜0.956), P = 0.045; OR = 0.682 (95% CI: 0.163˜1.201), P = 0.010, respectively) (Table 3) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For EPHX1 c.337T>C polymorphisms, the adjusted concentrations of CDR CBZ , CDR CBZE , CDR CBZD , CDR CBZE : CDR CBZ and CDR CBZD : CDR CBZE including 812 epilepsy patients were reported in 4 [7,8,25,31], 3 [7,8,31], 3 [7,8,31], 3 [7,8,17] and 3 [7,8,31] articles, respectively. A statistically significant association was found in the (TT vs CC) model for the adjusted concentrations of CDR CBZE (OR = -0.446 (95% CI: -0.811˜-0.0.081), P = 0.004) with high heterogeneity (I 2 =98.9%) (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations